Establishing dimensions of country attractiveness for cross-border second homes / Norliza Aminudin - Aminudin, Norliza (Universiti Teknologi MARA (UiTM), Malaysia, 2012)
The main purpose of this paper is to establish the dimensions of country attractiveness for long-term tourism. A country's attractiveness is studied from the perspective of wanting to have a cross-border second home (CBSH) in the host country by the current working expatriates, that is, their behavioural intentions. Based on the set of seventeen criteria of "touristic attractiveness" identified by Gearing, Swart and Var (1974) for short-term tourism, this study explores further country attractiveness in long-term tourism, specifically having a cross-border second home. An exploratory investigation, utilising a panel of experts is carried out to discover the dimensions and elements of Malaysia's attractiveness as host to a CBSH. The findings, using structural equation modelling (SEM) utilising 398 respondents suggest that there are three dimensions to Malaysia's attractiveness as a host to CBSH, which are climate and nature; value for money; and leisure activities. All three dimensions are significantly related to the overall satisfaction in living in the host country. Consequently, overall satisfaction has a direct effect on the behavioural intentions of having a CBSH in the host country. Based on the squared multiple-correlations, the relative magnitude of the country's attractiveness for having a CBSH is also established. The findings of the study provide a demonstration that dimensions found important in short-term tourism are still applicable in long-term tourism.